THE INFLUENCE OF PROBLEM-BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN MATHEMATICS IN CLASS IV UPTD SD NEGERI 73 BARRU DISTRICT BARRU - Yonathan S Pasinggi; Shasliani Shasliani; Selviana Selviana (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research is a type of quantitative research with a pre-experimental research design with a One Group Pretest-Posttest Design which aims to determine student learning outcomes in mathematics before and after using the problem-based learning model. The population in this study were all students of class IV UPTD SD Negeri 73 Barru totaling 30 students. The sample used was 30 students selected by saturated sampling technique. Analysis of the data used is the analysis of descriptive statistical techniques inferential statistical analysis. The results of descriptive statistics obtained from the results of class IV UPTD SD Negeri 73 Barru students before using the problem-based learning learning model were in the poor category and after using the problem-based learning learning model they were in the very good category. Then the results of the hypothesis testing were carried out by testing the Independent Sample T-Test showing a sig value (2-tailed) = 0.000 <0.05 meaning that the independent variable affects the dependent variable in other words H0 is rejected H1 is accepted. Thus it can mean that the problem based learning model learning has an effect on improving student learning outcomes on the material around and rectangular area of Class IV UPTD SD Negeri 73 Barru.